P432 Patient satisfaction and patient costs associated with telephone clinic appointments in Inflammatory Bowel Disease (IBD) following the pandemic. (30th January 2023) - Matini, L; Stokes, E A; Parra Mujica, F; Kormilitzin, A; Kantschuster, R; Punj Sharda, A; Dunbar, G; Song, K; White, L; Travis, S P L; Walsh, A
Abstract: Background: Prior to the COVID-19 pandemic, conventional management of outpatient care in IBD predominantly revolved around face-to-face clinic appointments. In the changing landscape of care provision during the pandemic, appointments were conducted almost exclusively through telephone consultation. An electronic questionnaire was developed to assess patient satisfaction and patient costs. Methods: A pilot was carried out with 15 patients to identify any technical issues with e-mail delivery of the questionnaire and gauge face validity of the questionnaire content. 1400 patients registered with the TrueColours-IBD remote digital monitoring system were sent the questionnaire link via e-mail in May 2021. No demographic data were collected by design, in order to avoid the perception of bias and ensure freedom of expression through anonymity. Results: 506 responses were received including 21 duplicates which were excluded, totalling 485 valid responses. 408/485 patients reported having a telephone appointment with the IBD service since March 2020, 484/485 reported having had a face-to-face appointment in the past. 348/408 (86%) were either 'very satisfied' or 'somewhat satisfied' with their most recent telephone consultation, while 22 (6%) were either 'very dissatisfied' or 'somewhat dissatisfied'. 247/408 (61%) were also either 'very satisfied' or 'somewhat satisfied' with the ease of accessing further care if required, compared to 33/408 (8%) who were either 'very dissatisfied' or 'somewhat dissatisfied'. Given the choice, 195/408 (48%) patients preferred to receive a telephone appointment in the future; 147/408 (36%) would opt for face-to-face and 66/408 (16%) stated no preference, all with the option of changing that choice if needed. Telephone appointments were associated with a mean total patient time off-work or leisure of 23 minutes (S.D. 51, n=408) compared to 190 minutes (S.D. 96, n=484) for face-to-face appointments. The average cost of time off work or leisure associated with telephone appointments was £5.55 (S.D. = £15.74, n=408), compared to £43.42 (S.D. = £31.27, n=484) for face-to-face appointments (Table 1). Costs of transport add further to face-to-face appointment costs. Greater proportions of patients had a companion for their face-to-face appointment and required childcare compared to telephone consultations (Table 2), which again increases the difference in costs. Conclusion: Almost half of surveyed patients stated a preference for telephone appointments, although a third still preferred traditional follow-up. An evolution of care pathways is supported by patient preference and the statistically significant time and cost savings to patients receiving telephone appointments.